PENGARUH INTENSITAS PROMOSI TERHADAP EKUITAS MEREK DAN KUALITAS LAYANAN SEBAGAI KEPUTUSAN PENGGUNAAN SHOPEEPAY (Studi Kasus Terhadap Pengguna ShopeePay di Kec. Duren Sawit Jakarta Timur) - Januar Syarifudin Ramdan (2021)
This study aims to prove and analyze the direct and indirect effect between promotion intensity, brand equity and service quality on the ShopeePay usage decision. The population of this research is ShopeePay users in the Kec. Duren Sawit, with a sample of 40 respondents based on the Proporsinate Stratified Random Sampling technique. This research is quantitative, with Structural Equation Modeling analysis in Partial Least Square method and using SmartPLS3.3 application. The Outer Model explains, the validity value (AVE) is above 0.5, the composite reliability value is above 0.7, the R-Square Adjusted is 57.3% for the usage decision, and has a model fit (NFI) of 69.3%. The Iner Model explains, (1)the direct effect of promotion intensity on usage decisions is 0.258 positive but not significant. (2)the direct effect of promotion intensity on brand equity is 0.732 positive and significant. And (3)the direct effect of promotion intensity on service quality is -0.168 negatif not significant. Furthermore, (4)the direct effect of brand equity on the usage decision is 0.572 positive and significant. And (5)the direct effect of service quality on the usage decision is 0.098 positive but not significant. Then, (6)the indirect effect of promotion intensity on the usage decision through brand equity is 0.419 positive and significant. Meanwhile, (7)the indirect effect of promotion intensity on the usage decision through service quality is -0.016 negative not significant. Keywords : Promotion Intensity, Brand Equity, Service Quality, Usage Decision, ShopeePay